Detection of a Novel Protein Encoded by the Bottom-Component RNA of Cowpea Mosaic Virus, Using Antibodies Raised against a Synthetic Peptide - Wellink, Joan (1987)
A peptide was synthesized that corresponded to a sequence in the cowpea mosaic virus bottom-component RNA-encoded 200-kilodalton polyprotein showing homology to the picornaviral 3C proteases. By injecting a rabbit with this peptide, antibodies were obtained that allowed the detection of a novel viral protein derived from the 200-kilodalton polyprotein. This protein, which had a size of 24 kilodaltons was found in both infected cowpea leaves and cowpea protoplasts.